Career Preferences of Medical and Nursing Students in Uttar Pradesh - Raha, Shomikho; Berman, Peter; Bhatnagar, Aarushi (World Bank, Washington, DC, 2013)
This note describes the career preferences of graduating medical and nursing students in Uttar Pradesh, with special reference to incentives offered for and work attributes of employment opportunities in rural areas. Results indicate that medical students prefer to concentrate on their post-graduate education and are not inclined to work in rural areas while nursing students have a greater predilection to work in public rural settings. The note draws attention to the fact that it is a tougher challenge to increase the supply of physicians in rural areas as compared to nurses and incentives offered to prospective health workers will be more effective ill the form of incentive packages.